The Use of the Carbonyl Group (C-3) of Isatin for the Construction of Pyrazoline Moiety and the Study of its Antioxidant Activity - Dawood, Rafid S.; Faisal , Farah N. (Iraqi Journal of Science, 2024)
A series of novel pyrazoline derivatives 5-13 were synthesized in three steps from isatin, with yields ranging from 40 to 72% over the multistep procedure. The first step included the condensation of isatin with p-aminoacetophenone to afford the corresponding Schiff base 1 in a 75% yield. In the second step, the enolate form of Schiff base 1 was reacted with different aromatic aldehydes (benzaldehyde, p-nitrobenzaldehyde, and p-chlorobenzaldehyde) to give the title chalcone derivatives 2-4 in 60-72 yields. In the third step, pyrazoline derivatives 5-13 were synthesized via cycloaddition reactions between compounds 2-4 and hydrazine hydrate, phenyl hydrazine, or p-nitrophenyl hydrazine. The cycloaddition produced the target pyrazoline compounds in 40-72% isolated yields. All prepared compounds were characterized by FT-IR and 1H NMR spectroscopy. Some of the prepared compounds were tested for antioxidant properties.